A retrospective chart review of the use of rituximab for the treatment of rheumatoid arthritis in Australian rheumatology practice. (16th October 2013) - Nicholls, Dave; Zochling, Jane; Boers, Anthony; Champion, Gary; Mathers, David; Riordan, John; Youssef, Peter; Scott, James; Griffiths, Hedley
Abstract Aim Rituximab is one of nine biologic agents approved for the treatment of rheumatoid arthritis (RA) in Australia. The primary study objective was to analyze the factors that lead to the therapeutic decision to use rituximab in RA. Method A cross‐sectional, retrospective chart review was conducted to identify patients who were treated with rituximab and to evaluate their response to treatment. Results Factors influencing the prescription of rituximab were identified. The most commonly reported reason for prescribing rituximab was the presence of comorbidities and the presence of seropositive disease. Median rituximab treatment duration was 32.5 months and mean number of treatment cycles was 4.1. Disease activity scores showed significant improvement from baseline to most recent visit. Rituximab treatment was well‐tolerated in this group of RA patients. Conclusions Rituximab was effective in a refractory group of RA patients and appears to be safe in a population with a high prevalence of comorbidities, including malignancy and recurrent infections/bronchiectasis. This study may assist rheumatologists in selecting appropriately targeted therapy in RA.